Faktor – Faktor Yang Mempengaruhi Derajat Keparahan Covid – 19 pada Pasien Hipertensi dan Diabetes Mellitus di RSUD Aji Batara Agung Dewa Sakti Kecamatan Samboja Kabupaten Kutai Kartanegara - Martasiah, Martasiah; Sutiningsih, Dwi; Widisuseno, Iriyanto (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: The high prevalence of Covid-19 affects the severity that leads to death, especially in patients who have comorbidities such as hypertension and diabetes mellitus. This study aims to determine the factors that influence the severity of Covid-19 in patients with hypertension and diabetes mellitus.Methods: Observational analytic research with a case control approach. The number of samples was 150 cases and 150 controls. The sampling technique was simple random sampling. Data analysis using chi square and multiple logistic regressionResults: Age (p=0.002), gender (p=0.033), smoking habit (p=0.004), central obesity (p=0.049), total cholesterol level (p=0.000), were found to be significant risk factors. While TB patients (p=797) was not a significant risk factor. Gender was found to be the most dominant risk factor with the highest OR of 14.55 (95% CI OR: 5.53-38.1).Conclusion: People infected with Covid-19 who have hypertension and diabetes mellitus can aggravate Covid-19. Men and women have the same chance of contracting Covid-19, but men have a higher risk due to hormonal influences and lifestyle. People should pay more attention to health protocols and organize a healthy lifestyle must be improved.Keywords: Covid 19, Degree of Severity, Comorbidities, Risk Factors